2002
DOI: 10.1080/00221320209598674
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Styles and Academic Achievement Among Filipino Students

Abstract: The authors' objective in this study was to determine whether the precepts of R. J. Sternberg's (1988, 1997) theory of mental self-government apply to a non-Western culture. They administered R. J. Sternberg and R. K. Wagner's (1992) Thinking Styles Inventory, which is based on the theory of mental self-government, to 429 Filipino university students. The results of item analysis, scale intercorrelations, and factor analysis were consistent with the general provisions of the theory. Correlational analysis betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 23 publications
(44 reference statements)
5
60
1
5
Order By: Relevance
“…According to research from Van der Walt [5] a learner's thinking style is a factor that influences the effective learning and teaching of mathematics and could predict achievement of mathematics in school. Bernardo and his colleagues [1] tried to apply Sternberg's theory of mental self-government applies to a non-Western culture. 429 Filipino university students responded to the inventory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research from Van der Walt [5] a learner's thinking style is a factor that influences the effective learning and teaching of mathematics and could predict achievement of mathematics in school. Bernardo and his colleagues [1] tried to apply Sternberg's theory of mental self-government applies to a non-Western culture. 429 Filipino university students responded to the inventory.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of education, scholars identified that thinking styles contribute significantly to students' academic achievement, learning approaches, cognitive development and social development [1,2]. Thinking styles also affect teaching behaviors, such as teaching approaches, interaction styles, and styles of humor [3].…”
Section: Introductionmentioning
confidence: 99%
“…El puntaje de cada estilo se formó con el promedio de las 8 respuestas correspondientes. La confiabilidad del instrumento ha sido reportada por otros autores en poblaciones distintas (Bernardo, Zhang y Callueng, 2002;Zhang, 2004 (Bernardo, Zhang y Callueng, 2002;Zhang, 2004).…”
Section: Instrumentounclassified
“…Se ha reportado que los EP orientados tanto a la creatividad como al conservadurismo influyen en el rendimiento académico, según el valor que les otorga el entorno educativo (Bernardo, Zhang y Callueng, 2002;Cano-García y Hughes, 2000;Zhang y Sternberg, 2000).…”
Section: Estilos De Pensamiento De Los Universitariosunclassified
“…In the field of education, scholars identified that thinking styles contribute significantly to students' academic achievement, learning approaches, cognitive development and social development (Bernardo, Zhang, & Callueng, 2002). Thinking styles also affect teaching behaviors, such as teaching approaches and interaction styles.…”
Section: Introductionmentioning
confidence: 99%